The excited spin-triplet state of a charged exciton in quantum dots. (8th July 2016) - Molas, M R; Nicolet, A A L; Piętka, B; Babiński, A; Potemski, M
Abstract: We report on spectroscopic studies of resonances related to ladder of states of a charged exciton in single GaAlAs/AlAs quantum dot structures. Polarization-resolved photoluminescence, photoluminescence excitation and photon-correlation measurements were performed at low ( T = 4.2 K) temperature also in magnetic field applied in Faraday configuration. The investigated resonances are assigned to three different configurations of a positively charged exciton. Together with a singlet ground state and a conventional triplet state (involving an electron from the ground state electronic s -shell), an excited triplet state, which involved an electron from the excited electronic p -shell was identified in single dots. The appearance of an emission line related to the latter complex is due to a partially suppressed electron relaxation in the investigated dots. An analysis of this emission line allows us to scrupulously determine properties of the excited triplet state and compare them with those of the conventional triplet state. Both triplets exhibit similar patterns of anisotropic fine structure and Zeeman splitting, however their amplitudes significantly differ for those two states. Presented results emphasize the role of the symmetry of the electronic state on the properties of the triplet states of two holes + electron excitonic complex.